TINGKAT PARTISIPASI MASYARAKAT DALAM PENGGUNAAN APLIKASI WEB DESA AKA-AKAE KECAMATAN WATANG SIDENRENG KEBUPATEN SIDENRENG RAPPANG - Kamiati Kamiati; Sapri Sapri; Sahar Sahar (PRAJA: Jurnal Ilmiah Pemerintahan, 2021)
Research objectives To determine the level of community participation in the use of web applications in Aka - Akae Village, to find out the factors that influence the level of community participation in the use of web applications in Aka - Akae Village. The population of this study was 499KK, while the research sample was 83 people. The data collection techniques used in this research are (1) observation, (2) decision study, (3) questionnaire, while using scalalicert data analysis technique. The collected data were then analyzed using a frequency table and using the SPSS 2.1 application. The results of the research on the level of community participation on the use of web applications in the Aka-Akae village, Watang Sidenreng district, were included in the "good" average category, namely 66.428%, in the good category, while the communication factor in increasing participation regarding the use of web applications in Aka-Akae Village 28 , 7%, the factor of community understanding in using web applications in Aka-Akae Village 18.9%, and the community's ability factor in using web applications in Aka-Akae Village 39.6%. This can be seen from the t test, where t count is 1.325% smaller than t table 1.993 when Ho is accepted, meaning it is not significant, so the level of community Participation has no significant effect on the use of Web applications.